Top income adjustments and inequality: an investigation of the EU-SILC - Carranza, R; Morgan, M; Nolan, B (Wiley, 2022)
This paper provides a novel assessment of how the World Inequality Database (WID) top income adjustment applied by Blanchet, Chancel, and Gethin (2021) to European Union Statistics on Income and Living Conditions (EU-SILC) data for 26 countries over 2003–2017 for Distributional National Accounts purposes affects inequality in equivalized gross and disposable household income. On average, the Gini is increased by around 2.4 points for both gross and disposable income, with notable differences across countries but limited impact on trends. EU-SILC countries that rely on administrative register data see relatively small effects on inequality. Comparing with two other recent studies, differences in impacts on measured inequality depend less on the adjustment method and more on whether external data sources are used.